Forage productivity and morphogenesis of Mesosetum chaseae under potassium fertilization (Research, Society and Development, 2022)
The effect of potassium levels (0, 50, 100 and 200 kg of K2O ha-1) on green dry matter (GDM) yield and morphogenetic and structural characteristics of Mesosetum chaseae (Luces) was evaluated under natural field conditions. Potassium fertilization increased significantly (P